LAYANAN KONSELING INDIVIDUAL BAGI SISWA YANG MENGALAMI KESULITAN BELAJAR PADA KELAS VII DI MTS NEGERI MULAWARMAN BANJARMASIN - Noorlatifah Noorlatifah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2015)
AbstracThe background of this research that the class VII are learners with learning difficulties by reason of lazy, silent as the students were told to read in class, and the impact if not addressed there will be such a shame when school because often mocked, low confidence, and finally affect the value of raportnya there is not reached KKM (Criterion Complete Minimal). In this case it is necessary to hold a study that Individual Counselling Service for Students Who Have Learning Difficulties In Class VII in public MTs Mulawarman Banjarmasin.    This type of research is descriptive-quantitative method, the research aims to describe (draw) a symptom. This study places at MTs Mulawarman Banjarmasin. The population in this study amounted to 16 people. The sampling technique using total sampling. Total sampling is a sampling technique in which the number of samples is equal to the number of population .Teknik data collection using interviews and questionnaires.   The results showed that the forms of learning difficulties experienced by students of class VII is a learning disorder that is equal to 63%, slow learner at 25% and under achiver is equal to 12%. Factors that cause learning difficulties seventh grade students are factors inter consisting of physiological and psychological factors, while external factors which consisted of factors school environment, family and community. The next phase of the services of individual counseling for students who have difficulty learning to take several steps include identification of students, setting up appointments, preparing the place and the technical implementation of services, establish service facilities, identification and exploration of the problem, discuss students' problems by using techniques, encouraging alleviation students, strengthen the commitment of students to alleviate the problem, evaluate and analyze the results of the evaluation.Keywords: individual counseling services, learning difficulties.